DESCRIPTION of Lannea coromandelica Houtt. Merrill. AS MEDICINAL PLANT: A REVIEW - Meutia Zahara; Suryady Suryady (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2023)
Indonesia is a big country consists of more than 400 ethnics and sub-ethnics spread throughout Indonesian territory Such as Sumatra, Java, Kalimantan, Sulawesi, and other areas. This country is rich in natural resources and the society still use plants to cure some diseases as it has no side effects, easy to grow and easy to find as well it’s cheap. The development of traditional medicine has been growing rapidly, especially herbal medicine or medicine derived from plants that is being produced at industrial scale. Lannea coromandelica Houtt. Merrill. known as horse tree or male kedondong In Indonesia and Indian Ash tree in world wide. This plant is widely used as a medicine to cure gout arthritis, cholera, dysentery, sore yes, dyspepsia, leprosy, sprains, bruises, wound healing, snake bites and others. Some researches mentioned that this plant also has the benefits as an antidiabetic and anti-inflammatory. This manuscript was written to gathered some important information’s about botanical features, phytochemicals content and the benefits of Lannea coromandelica Houtt. Merrill. as medicinal plant Keywords: Lannea coromandelica, Indian Ash tree, medicinal plant